Udział osób trzecich (sąsiadów) w postępowaniach z zakresu utrzymania obiektów budowlanych. - Fronczak, Andrzej (Kwartalnik Prawa Publicznego, 2015)
In principle, an owner or an administrator of a construction object is a party in administrative proceedings connected with the maintenance and usufruct of such construction object. The participation of neighbours in such proceedings is exceptional. It is also treated as exceptional in court and administrative judicial decisions. However, it does not rule out the situation where third parties obtain the status of a party, provided that they show legal interest based on a specific legal norm which may result not only from the administrative law but also from other bodies of law, for instance: civil law.